Classification of moving objects using active vision - Bilal, Sara Mohammed Osman Saleh; Abu-Bakar, Syed A.R (2005)
An offline system that is capable to detect the moving object and classify it into three classes: "Human, Vehicle and Animal" is presented. The detection of the target based on Background Subtraction technique. The classification makes use ofboth static and dynamic features ofthe moving objects. All features are sequentially arranged to improve the classification significantly